GAMBARAN UMUM PENGARUH FERMENTASI TERHADAP KUALITAS NUTRISI AMPAS SAGU SEBAGAI PAKAN BROILER: An Overview impact of quality pith sago fermented as broiler feed - Tharukliling, Selvia (STIPER Santo Thomas Aquinas Jayapura, 2022)
Sago pith waste have the potential to be used as alternative animal feed by first carrying out a fermentation process because sago pith contain high crude fiber around of 30.14% and crudeprotein 4.37%. After being fermented with the right microorganism as a decomposer of crudefiber, it turns out that the nutritional yield of sago pith increased dramatically, namely Crudeprotein of sago pith after fermentation with Neurospora crassa 15.52 – 17.78%, fermented withaspergillus niger result With such changes in nutrition, fermented sago pith can be used aspoultry feed for both broiler, laying and chickens.